Synthesis of 1,2,4-Triazole Derivatives and Determination of Protonation Constant - Islamoglu, Fatih; Kahveci, Bahittin; Bekircan, Olcay (Asian Journal of Chemistry, 2010)
A microwave irradiation method has been developed for the synhesis of some 1,2,4-triazole derivatives using environmentally benign solvent ethanol in open vessels. Twelve 1,2,4-triazole derivatives were synthesized in good yields. The newly synthesized compounds (2a-f and 3a-f) were titrated potentiometrically with tetrabutylammonium hydroxide in isopropyl alcohol, t-butyl alcohol, acetonitrile and N,N-dimethyl formamide (DMF) and the half-neutralization potential values and the corresponding pKa values were determined.